44. SAFTY PATIENT CULTURE OF HEALTH STAFFS IN HUNG VUONG GENERAL HOSPITAL, 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the situation and associated factors of safety patient culture among health staffs in Hung Vuong General Hospital, 2024.Objects and methods: This is a cross-sectional study using a semi-structured questionnaire to interview 328 healthcare workers at Hung Vuong General Hospital from December 2023 to July 2024. The study used the survey on patient safety culture tool from AHRQ. Data were analyzed using SPSS 20.0 software.Results: The positive response rate of the patient safety culture among healthcare workers at Hung Vuong General Hospital was 69.5%. There was a statistically significant association between factors such as working years at hospital, working years at faculty and the job title of health staffs with feedbacks about patient safety.Conclusion: It is necessary to maintain and improve the strengths in the patient safety culture among healthcare workers at Hung Vuong General Hospital, Phu Tho, such as Teamwork within departments, Continuous learning and improvement and Department leaderships encourage patient safety.
Keywords: Patient safety culture; health staff